Determinants of Patient Satisfaction with Discharge Pharmacy Services at a Tertiary Care Center in Jeddah, KSA - Alzahrani AM; Rambo R; Alotain F; Naeem A; Alzhrani RM; Albaradi MA; Althubiani S; Sharaf SE; Alwadie AF; Alzahrani MS; AlSebaih NT; Ainosah RH; et al. (Dove Medical Press, 2024)
Abdullah M Alzahrani,1- 3,* Razan Rambo,1- 3 Fahad Alotain,1- 3 Anjum Naeem,1- 3 Rami M Alzhrani,4 Mohammad A Albaradi,1- 3 Shoeb Althubiani,1- 3 Shahd E Sharaf,1- 3 Ali F Alwadie,1- 3 Mohammad S Alzahrani,5 Noor T AlSebaih,6 Randa H Ainosah,7 Yahya A Alzahrani7,* 1Pharmaceutical Care Department, Ministry of National Guard-Health Affairs, Jeddah, 22384, Saudi Arabia; 2King Abdullah International Medical Research Center, Jeddah, 21423, Saudi Arabia; 3College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Jeddah, 22384, Saudi Arabia; 4Department of Pharmaceutics and Industrial Pharmacy, College of Pharmacy, Taif University, Taif, 21944, Saudi Arabia; 5Department of Clinical Pharmacy, College of Pharmacy, Taif University, Taif, 21944, Saudi Arabia; 6Pharmaceutical Care Department, King Fahad Armed Forces Hospital, Jeddah, 23311, Saudi Arabia; 7Department of Pharmacy, East Jeddah Hospital, Ministry of Health, Jeddah, 23816, Saudi Arabia*These authors contributed equally to this workCorrespondence: Yahya A Alzahrani, Department of Pharmacy, East Jeddah Hospital, Ministry of Health, Jeddah, 23816, Saudi Arabia, Tel +966557700178, Email yalzahrani5@moh.gov.saPurpose: Patient satisfaction with pharmacy services, particularly in outpatient and discharge pharmacy settings, has become a vital metric for assessing medical quality. However, there's limited research on patient satisfaction in discharge pharmacy services in the Kingdom of Saudi Arabia (KSA). This study aims to systematically investigate and delineate the various patient-related and non-patient-related factors that significantly impact patient satisfaction in the realm of discharge pharmacy services.Patients and Methods: This cross-sectional study was conducted over three months at King Abdulaziz Medical City in Jeddah (KAMC-J). The sample size was determined using a single population proportion formula, which resulted in a required sample size of 384 patients. A validated questionnaire with a five-point Likert scale evaluated satisfaction from "Strongly Dissatisfied" (1 point) to "Very Satisfied" (5 points) has been used. Data collectors underwent training and obtained written consent from participants, with questionnaire completion taking 5- 10 minutes face to face.Results: The study encompassed 437 participants, primarily male (59%) with a college education (45.3%), residing mostly in Jeddah (67.3%). Notably, 84.4% were not healthcare providers, and most visited the pharmacy every six months (44.6%). The patient satisfaction survey revealed high scores for counseling understanding, pharmacist courtesy, and the way the pharmacist answered questions (4.94± 0.31, 4.94± 0.27, 4.94± 0.32; respectively), but lower for understanding possible side effects (4.30± 1.30) and pharmacy location (4.57± 0.99). In logistic regression, visits lasting 10- 15 minutes, and less than 10 minutes were significantly (p< 0.05) associated with increased odds of patient satisfaction (OR=6.39, OR=9.45; respectively) Moreover, the medium length hospital stay was associated with decreased odds of patient satisfaction (OR=0.31, p=0.026).Conclusion: In conclusion, the study determined a significant proportion of patients are satisfied with discharge pharmacy services at KAMC-J, with the length of consultation and hospital stay being pivotal to their satisfaction. Addressing these factors, alongside optimizing pharmacist-patient communication and pharmacy service efficiency, can substantially elevate the quality of pharmaceutical care and patient experience.Keywords: King Abdulaziz medical city, KAMC-J, Discharge pharmacy, Patient Satisfaction, Counseling Services, Pharmacist-Patient Relationship, Pharmacy Location and Environment